RETRACTED ARTICLE: Inhibition of airway inflammation in a cockroach allergen model of asthma by agonists of miRNA-33b - Ruichao Niu (Nature Portfolio, 2017)
Abstract MicroRNAs (miRNAs) play powerful roles in immune function by regulating target genes that mediate cell behavior. It is well known that mast cells have essential effector and immune regulatory functions in IgE-associated allergic disorders and in innate and adaptive immune responses. However, the role of miRNAs in mediating mast cell functions and the relevant mechanisms require further exploration. The roles of miR-33b in airway inflammation and mast cell functions are still unknown. To examine the role of miR-33b in mouse mast cells in cockroach allergen-induced asthma, we developed a lentiviral system for miRNA-33b overexpression to examine whether miRNA-33b mediates airway inflammation by regulating mast cell function and to evaluate the underlying mechanism. The results showed that miR-33b inhibited cockroach allergen-induced asthma in vivo: in particular, it inhibited TH2 cytokine production. In addition, we found that in cells in which miRNA-33b had been transfected, mast cell degranulation was inhibited through suppression of the calcium release and IgE/FcεRI pathway. Our study provides new insight into the roles of miR-33b in asthma and mast cell biology and identifies novel mechanisms that may contribute to mast cell-related pathological conditions in airway inflammation.